Expressions of ABCG2, CD133, and Podoplanin in Salivary Adenoid Cystic Carcinoma. (6th April 2014) - Li, Wuwei; Tamamura, Ryo; Wang, Bo; Liu, Qigui; Liu, Han; Liu, Tingjiao; Katase, Naoki; Xiao, Jing; Nagatsuka, Hitoshi
Abstract : Adenoid cystic carcinoma (ACC) is one of the most common salivary gland malignant tumors with a high risk of recurrence and metastasis. Current studies on cancer stem cells (CSCs) have verified that CSCs are the driving force behind tumor initiation and progression, suggesting that new cancer therapies may be established by effectively targeting and killing the CSCs. The primary goal of this study is to investigate the expression patterns of ABCG2, CD133, and podoplanin in ACC of minor salivary glands by immunohistochemistry analysis. We found that ABCG2 was weakly expressed in normal looking salivary gland tissues. A significant upregulation of ABCG2 expression in ACC was observed with a similar expression pattern of Ki-67. CD133 was detected in apical membrane of epithelial cells and podoplanin was expressed positively in myoepithelial cells of both normal looking tissue and ACC. However, no significant difference was found of the expression pattern of CD133 and podoplanin between normal looking tissues and ACC. Our observations suggest that CSCs may exist in quiescent cells with ABCG2 positive staining, which are surrounded by cells with positive expression of ABCG2 and Ki-67 in ACC, and costaining with ABCG2 and Ki-67 may help predict the location of CSCs.